Lima, ciudad renacentista - Bonilla Di Tolla, Enrique (2015)
This article establishes the relevance of calling Lima a renaissance city. This, both due to the time in which it was founded, on the 16th century, and to the accordance of its layout with models that arose from architectural theorists during the Renaissance, that as it would be shown later also coincide with Roman paths, unknown until the 18th century.